1988
DOI: 10.1073/pnas.85.19.7312
|View full text |Cite
|
Sign up to set email alerts
|

Ly-1 B-cell clones similar to human chronic lymphocytic leukemias routinely develop in older normal mice and young autoimmune (New Zealand Black-related) animals.

Abstract: Studies presented here demonstrate that individually expanded clones of murine Ly-1 B cells, perhaps analogous to the expanded neoplastic Leu-1 B-cell clones in human chronic lymphocytic leukemias, are universally detectable in young New Zealand Black (NZB)-related autoimmune mice and in senescent normal mice (>18 months old). These clones are visible as phenotypically homogeneous cell populations in multiparameter fluorescence-activated cell sorter analyses of peritoneal and splenic B cells; they show unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 27 publications
6
77
0
Order By: Relevance
“…Genetically susceptible autoimmune strains of mice also manifest increased numbers of CD5+ B -PHA cells (termed Ly-l), which produce autoantibodies such as anti-erythrocyte and anti-DNA (15). Aged autoimmune mice develop clonal proliferation of Ly-l+ B cells that may be analogous to the B cell lymphomas that arise in humans with primary SS (16,17). In normal mice, Ly-l+ B cells produce growth factors and express helper activity (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically susceptible autoimmune strains of mice also manifest increased numbers of CD5+ B -PHA cells (termed Ly-l), which produce autoantibodies such as anti-erythrocyte and anti-DNA (15). Aged autoimmune mice develop clonal proliferation of Ly-l+ B cells that may be analogous to the B cell lymphomas that arise in humans with primary SS (16,17). In normal mice, Ly-l+ B cells produce growth factors and express helper activity (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice demonstrated that a cell analogous to the human CD5-t B cell and expressing cell surface Ly-1 is increased in number in autoimmune mice and becomes clonal in aged mice (15)(16)(17). Recent studies in normal mice suggest that these unusual B cells may have regulatory properties and helper function (18).…”
Section: B Cells Expressing Cd5 Are Increased In Sjogren's Syndrome Mmentioning
confidence: 99%
“…16 Mononuclear cells were isolated by using density gradient separation kit (HISTOPAQUE-1077, Sigma) from mouse periphery blood, according the manufacturer's instruction.…”
Section: Isolation Of Peritoneal Cells and Peripheralblood Mononucleamentioning
confidence: 99%
“…B-1 cells represent the cell of origin for human chronic lymphocytic leukemia, the malignant B cells of which typically express CD5 (40). In mice, monoclonal expansions of B-1 cells that resemble chronic lymphocytic leukemia develop in almost all individuals with increasing age; furthermore, New Zealand Black mice, which contain increased numbers of B-1 cells, develop several types of B-1-derived lymphomatous malignancies early on (41,42). These associations with autoimmune and malignant dyscrasias further impel the drive to understand the regulation of B-1 cell development and activity.…”
mentioning
confidence: 99%